2015
DOI: 10.1007/s10592-015-0703-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of a head-start program to guide conservation of an endangered Galápagos tortoise (Chelonoidis ephippium)

Abstract: Critically endangered wildlife species typically require intensive management using a variety of in situ and ex situ approaches. Yet, despite broad application of ex situ conservation strategies, comparatively few programs incorporate genetic tools into management decisions and monitoring efforts. This is the case with the giant Galá-pagos tortoise endemic to Pinzón Island (Chelonoidis ephippium); a head-start program has been in place for 50 years without an evaluation of whether this conservation interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…One persistent pattern found in all previous studies of Pinzón giant tortoises using microsatellites has been heterozygote deficit relative to Hardy–Weinberg expectations and significantly positive inbreeding coefficients (Beheregaray, Ciofi, Caccone, Gibbs, & Powell, ; Garrick et al., ; Jensen et al., ). Similar results were found in a recent study employing double‐digest RAD (ddRAD) sequencing to quantify genetic diversity and reconstruct population structure across all 12 extant species of Galapagos giant tortoises (Miller et al., ).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…One persistent pattern found in all previous studies of Pinzón giant tortoises using microsatellites has been heterozygote deficit relative to Hardy–Weinberg expectations and significantly positive inbreeding coefficients (Beheregaray, Ciofi, Caccone, Gibbs, & Powell, ; Garrick et al., ; Jensen et al., ). Similar results were found in a recent study employing double‐digest RAD (ddRAD) sequencing to quantify genetic diversity and reconstruct population structure across all 12 extant species of Galapagos giant tortoises (Miller et al., ).…”
Section: Discussionmentioning
confidence: 89%
“…No population structure was evident between temporal samples based on STRUCTURE or DAPC clustering analyses, although there were very small, but significant, Phi ST values (Table ). A previous microsatellite‐based study of Pinzón giant tortoises found mixed evidence in tests for a bottleneck, with no genetic signature of population decline in heterozygote excess tests, a normal distribution in the mode‐shift test indicating a stable population size, and M ‐ratio tests suggesting a population bottleneck (Jensen, Tapia, Caccone, & Russello, ). Unfortunately, in this study, we were unable to explicitly test for genetic signatures of a bottleneck in the Pinzón tortoise contemporary samples given the lack of an appropriate mutation model for SNPs using the conventional heterozygote excess test (Cornuet & Luikart, ) and the fact that the size of our data set precluded the application of site frequency spectrum‐based methods (e.g., Excoffier, Dupanloup, Huerta‐Sanchez, Sousa, & Foll, ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, evaluations of headstarting as an intervention can encompass projects using turtle eggs from any source, although selective pressures (e.g., local adaptation, artificial selection) warrant consideration in evaluations of post-release success. Although this selection is unlikely to be as strong in captive turtles because of their different mating strategies and long generation times (but see Jensen et al 2015), selection on hatchery-raised fish can have major impacts on post-release survival (Le Cam et al 2015;Jensen et al 2016), and this possibility should not be discounted in other taxa.…”
Section: Example Intervention: Headstartingmentioning
confidence: 99%